Performance evaluation of programming languages - Singh, Priya; Shukla, Satyam; Chandra, Subhash; Dixit, Vimal (ICIIECS '17 : proceedings of 2017 International Conference on Innovations In Information, Embedded and Communication Systems : Coimbatore, India, 17th 7 18th March 2017, 2017)
In the world of computer, languages used for the purpose of communication are known as programming languages. These languages are used to do the interaction between various other parts of computer and other machines. There is the long list of such languages which are widely used in this field, some of them are existing from long time while some are developed and were used for certain period of time and right now some of them are out of use. Here in this paper we basically did the comparison between array programming language and compiled programming languages besides this we also discussed about the concurrent, imperative and declarative languages. We further classified the imperative and declarative languages. We saw the dependency of languages on memory as we took the program of factorial in various languages as a result some of the programming languages used here terminated and provided the wrong output on giving the large value as input. As in case of factorial, if we have to perform the computation of nth number then we have to do the computation of (n-1)th term first which takes large memory size in static memory allocation while it can be easily done through dynamic allocation of memory as it does the use of runtime memory allocation concept. So, as we increase the input values most of the languages fails and result to lead wrong output.